Altruism At One-Day-One-Thousand Alms Community In Bengkulu City - Ammarsan Fahchory MS (Jurnal Kajian Islam Interdisipliner, 2022)
This study aims to analyze altruism at One-day-one-thousand Alms Community (Komunitas Sedekah Seribu Sehari) in Bengkulu City. This study is a qualitative research with phenomenology approach. The purposive sampling was used for the selection of key informants. Data collection techniques were carried out through: interviews, observation and documentation. The research findings indicate that there are two types of altruistic behavior at this community, namely internal and situational altruism. Internal altruism was clearly seen in which people did not expect anything except for positive emotion. They only did hope for blessing of Allah (God) and show a high empathy. Situational altruism indicated that people needed a support from beloved family like husband and father, attractiveness, having a leisure, modelling. Besides, this community exhibited altruistic behavior that they prioritized their closest family first and they helped others, then. [Penelitian ini bertujuan untuk menganalisa perilaku altruisme pada Komunitas Sedekah Seribu Sehari di Kota Bengkulu. Penelitian ini merupakan penelitian kualitatif-fenomenologi. Informan dipilih dengan teknik purposive sampling. Data dikumpulkan dengan teknik wawancara, observasi dan dokumentasi. Hasil penelitian ini menunjukkan bahwa: pada komunitas Sedekah Seribu Sehari ditemukan beberapa perilaku altruisme diantaranya adalah altruism internal dan altruism situasional. Altruism internal ditandai dengan membantu dengan tidak mengharapkan apapun kecuali emosi yang positif, hanya mengharap ridho Allah SWT, dan memiliki empati yang tinggi. Altruism Situasional ditandai dengan perlunya dukungan dari orang-orang tersayang seperti suami dan ayah, daya Tarik, memiliki waktu luang, dan modelling. Selain itu, komunitas sedekah seribu sehari mempunyai bentuk altruism kerabat di mana lebih mendahulukan membantu keluarga terdekat kemudian membantu orang lain.]